2020
DOI: 10.2147/cmar.s276022
|View full text |Cite
|
Sign up to set email alerts
|

<p>Regulatory Networks of LncRNA MALAT-1 in Cancer</p>

Abstract: Long noncoding (lnc)RNAs are a group of RNAs with a length greater than 200 nt that do not encode a protein but play an essential role in regulating the expression of target genes in normal biological contexts as well as pathologic processes including tumorigenesis. The lncRNA metastasis-associated lung adenocarcinoma transcript (MALAT)-1 has been widely studied in cancer. In this review, we describe the known functions of MALAT-1; its mechanisms of action; and associated signaling pathways and their clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 204 publications
(223 reference statements)
1
41
0
Order By: Relevance
“…Sox2ot acts as a miRNA sponge to the miR-200 family, upregulates Sox2 expression, and promotes EMT and stemness, suggesting that Sox2ot can accelerate invasion and metastasis of PDAC ( Li et al, 2018 ). MALAT-1 is one of the well-known oncogenic lncRNAs that act in diverse tumors, such as lung, hepatocellular or gastric cancers ( Fu et al, 2020 ). ( Jiao et al, 2015 ) reported that MALAT-1 promotes the EMT process and generates cancer stem cells (CSCs).…”
Section: The Functional Roles Of Selected Lncrna In Emt Of Pdacmentioning
confidence: 99%
“…Sox2ot acts as a miRNA sponge to the miR-200 family, upregulates Sox2 expression, and promotes EMT and stemness, suggesting that Sox2ot can accelerate invasion and metastasis of PDAC ( Li et al, 2018 ). MALAT-1 is one of the well-known oncogenic lncRNAs that act in diverse tumors, such as lung, hepatocellular or gastric cancers ( Fu et al, 2020 ). ( Jiao et al, 2015 ) reported that MALAT-1 promotes the EMT process and generates cancer stem cells (CSCs).…”
Section: The Functional Roles Of Selected Lncrna In Emt Of Pdacmentioning
confidence: 99%
“…MALAT-1 was firstly discovered in non-small cell lung cancer [96,97]. However, high expression of MALAT-1 has been found in various cancer tissues including pancreatic cancer [63,98,99]; therefore, MALAT-1 is considered as an oncogenic lncRNA. In pancreatic cancer, increased expression of MALAT-1 promoted cell growth, migration, and invasion [59].…”
Section: Malat1mentioning
confidence: 99%
“…MALAT1 is one of the earliest discovered and best-characterized lncRNAs with its primary role in cancer (reviewed in the work of [88]). However, it was also reported to be involved in retinal pathologies.…”
Section: Long Non-coding Rnas In Amd Modelsmentioning
confidence: 99%